Sistem Pendukung Keputusan Pendataan Warga Penerima Bantuan Raskin dengan Menerapkan Metode Weight Aggregated Sum Product Assesment (WASPAS) - Mesran Mesran; Rosmita Sari; Ridha Maya Faza Lubis; Muhammad Syahrizal (Journal of Computing and Informatics Research, 2026)
Raskin (rice for the poor) is a rice program for the poor. The Raskin program is one of the government's efforts to reduce the burden of expenditure on poor families. However, in practice, decision-making for determining the criteria for rice recipients usually does not refer to the criteria of poor families, resulting in misdirected rice distribution. To address this issue, a decision support system will be developed to assist in the targeted distribution of Raskin using the Weighted Aggregated Sum Product Assessment (WASPAS) method. This research was conducted by finding the weight value for each attribute, then a ranking process was carried out to determine the best alternative. The criteria used were: Type of Employment, Income, House Condition, Family Size, Age. The results of the study recommend that alternative 4, with the highest score of 0.676, be selected to receive Raskin assistance